Waves of Feminism in the Global World: A Case Study of Pakistan (1958-2008) - Ms. Sabira Iqbal (Journal of Peace, Development and Communication, 2022)
Feminism refers to a set of movements and beliefs focused on defining, developing, and achieving gender equality. Since the beginning of recorded history, women have been oppressed for their views and conduct. Feminism arose primarily in response to various traditions that restricted women’s rights, but it is a global revelation and contradiction. The presentation begins with an overview of feminism’s origins and the various layers of feminism that have emerged in the global community over the last two centuries. It also goes over the various varieties of feminism and how they relate to the various waves that have emerged. The report then goes on to discuss Pakistan’s feminism phase, which will be broken down into layers. The last section of the paper contains the conclusion.